Estimating the water requirement of wheat crop using remote sensing techniques (Damascus University Journal of agriculture sciences, 2026)
This research aimed to estimate the water requirement of the wheat crop using remote sensing techniques (satellite images), in the village of Zbdin in Damascus Countryside Governorate/Syria, during the year (2021-2022), where the water requirement was first calculated in the traditional way, relying on organized tables of FAO and the Penman-Montes equation. Based on accurate climate data. The water requirement estimated by this method reached (369.76 mm).Secondly, calculating the requirement using remote sensing techniques, relying on the vegetation index (NDVI) from satellite images of the Sentinel-2 L2A satellite to calculate the yield factor, and calculating evapotranspiration from images uploaded from (Wapor) site. This method is reduced effort, time and cost, he water requirement reached (357.682 mm) in this way.The statistical analysis of water requirement between the results of the two methods showed that the correlation coefficient was 97% and the efficiency was 98%, as they behave the same during the different growth stages of the crop, as it was low at the beginning of the season and then increased to reach a peak in the maximum growth stage (mid-season) and after that it began to decrease due to. maturity and harvest.Statistical analysis of the crop coefficient was also conducted, and it was found that the crop coefficient calculated based on the plant index from satellite images behaves the same way as the crop coefficient measured from FAO tables during various growth stages. Besides, it was low at the beginning of the season, then increased to reach a peak in the maximum growth stage, then it decreased due to maturity, dryness of the crop, and harvest, and the correlation coefficient between them was 84%.
Keywords: Water Requirements; Remote Sensing; NDVI; Crop Coefficient; Satellite Images